International organizations’ evolutionary impacts: “The good, the bad and the ugly”? - Bitsch, Marion (Austria, 2025)
Digitalization and globalization have changed the ways firms conduct their activities, multinational business enterprise (Coviello, Kano, & Liesch, 2017; Vahlne & Johanson, 2017) or global service firms (Kundu & Lahiri, 2015; Rammal & Rose, 2014) are now mainstream. This calls for a review of firms’ value creation evaluation in relation to ethics. The use of traditional economic performance indicators is less and less relevant as business metrics (Yoon, 2017) and what’s more performativity is social problematic (Fleming & Banerjee, 2016).
The objective of this conceptual paper is to enable theoretical development regarding organization behavior and export promotion and financing, with a focus on the account of the stakeholders’ interests and CSR. I do a critical analysis on how and why EPOs produce the status quo among firms through their support. After understanding some of the root causes of this situation, I discuss what could be done in order to move towards supporting “corporate citizenship” (Banerjee, 2001, 2008, 2018b) oriented firms.
Regarding contributions this is the first time a research links the behavioral theory of the firm, CSR and the evolutionary mismatch hypothesis.
IACCM-IÉSEG Research Conference: Intercultural competencies for a disruptive VUCA world: Exploring creativity, innovation, resilience & resistance in intercultural research, training & management, Conference Proceedings